Perbedaan gender dalam memilih lembaga pendidikan ditinjau dari teori pilihan rasional James S. Coleman - Nur Hidayatus Sa'adah (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2022)
In the educational process, the environment has a major influence in the formation of student behavior. The current education process in Indonesia seems to be still dominated by gender. In general, Indonesian people still hold the view that women are a second-class group and have a lower status than men. Whereas in the world of education, all humans, both men and women, are equally entitled to education. Education, which is a male and female field of study, is in fact more valued by men than women. This situation is caused by patriarchal views, especially the view that men have a higher position and qualification than women. Gender affects the motivation to choose an educational institution. This article discusses the differences between men and women in choosing an educational institution. Most men prefer the SMK (vocational high school) level and women choose SMA (general high school) because men think that after graduating, they will work with what they have acquired during the SMK. Meanwhile, on average, more women choose to continue their studies to college.